Screening for actinomyces isolated from soil with the ability to inhibit Xanthomonas oryzae pv. oryzae causing rice bacterial blight disease in Vietnam - Phan Thi Phuong Hoa (African Journal of Biotechnology, 2016)
Bacterial blight disease caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the major diseases in rice culture of Northen Vietnam, as well as other rice-growing regions of the world. In this study, we isolated and screened for actinomycete strains from Vietnam with the ability to inhibit Xoo isolates from northern Vietnam. From 90 actinomycete strains taken from soil in northern Vietnam in 2010, we screened for their antagonistic activity against 10 races of Xoo causing rice bacterial blight disease. Three actinomycete strains were found to inhibit all 10 Xoo races. Among the three strains, a strain namely VN10-A-44 was shown not to have the ability to produce toxic compounds and was selected for further study. The strain was identified as Streptomyces virginiae by 16S ribosomal RNA gene sequencing. We replaced soybean meal with tofu waste in antibiotic producing medium to improve antagonistic activity of VN10-A-44 against the Xoo pathogen and to make use of tofu waste for large-scale fermentation of VN10-A-44. We found that replacing soybean meal with 20 and 30 g of tofu waste/litter in the antibiotic producing medium gave the largest inhibition zone against the Xoo pathogen